Comparing the Importance of Luxury Value Perceptions and Purchase Intentions between Modern Believers and Non-modern Believers in Malaysia - Tiong, Jian Xi (2013)
Segmenting the population assisting marketers to bridge the gap of the rapid changes based on uncertainties of desirable needs and wants. One of the most noticeable market segments throughout the studies is psychographic segmentation by adopting both psychology (e.g. lifestyle) and demographic profile (e.g. age) bases. The objectives in this study is to examine the value perceptions of modern believers and non-modern believers, quantitative approach is adopted as this suited the best for descriptive and casual research. Independent t-test, partial least squares structural equation modelling (PLS-SEM) and partial least squares multi-group analysis (PLS-MGA) techniques were adopted to analyse the collected data. The findings suggest that, in general, consumers in Malaysia perceived combination of price and quality values (positive relationship) are equally important than expressive values. Whereas, modern believers deemed to have greater self-directed value perceptions and functionality value perceptions than non-modern believers. In short, this results is aimed to assist luxury brand managers in Malaysia to develop a coherent and integrated long-term strategy that fits into this unique yet collectivism society.